L’ḥarga e le sue bruciature. Riflessioni sulla migrazione “irregolare” tunisina a partire da alcune note etnografiche - Carmelo Russo (Archivio Antropologico Mediterraneo)
The purpose of this contribution is to analyze 'the burnings' of the ḥarga, the crossing of the Mediterranean made by migrants without passports and visas, by which documents and identities, borders and boundaries are burned, as the etymon of the verb ḥaraqa suggests, starting from ethnographic material collected “first-hand.” 'Stopping' on the stories of those who experienced and/or imagined the ḥarga returns innovative and original approaches, subtracting the protagonists from stereotypes and simplifications, in which personal ambitions and desire for change emerge emphasized by post-Spring disillusionment and a stagnant condition of the “youth,” distrustful of the Tunisian future. At the same time, it reveals how experiences are largely permeated by inequalities at the geopolitical level between the global North and South. In a plurality of attitudes, meanings not unambiguous in perceptions and moral valences, toward which the subjects themselves surrender to an ambivalence in which stigma and exculpation stand in dialectical relation, the ḥarga allows them to escape the procrastination of uncertainty and disheartenment and to challenge the normative state of immobility due to the construction of illegality and illegitimacy. The ḥarga will emerge in the form of collective representations capable of permeating the singularities of existences in which awareness of the difficulties due to visa restrictions, the paternalism of the “Western” gaze, the postcolonial subservience to Europe, the limitations of qualifying as “legal migrants,” the violence and aggressiveness of controls, and the European will to exclude undesirables play a prominent role.